Prediction analysis of the length of time for changes in the status of positive patients for covid-19 delta and omicron variants using the markov chain model - Haryanto, Dwi; Addini, Fida Fathiyah (Desimal: Jurnal Matematika, 2022)
In this research, a Markov chain model was constructed from the conditions that might be experienced by the people during the Delta or Omicron variant of the COVID-19 pandemic. This condition is divided into 3 states; "0" indicates a healthy condition, "1" indicates the state of being infected with COVID-19, and "2" indicates the death state. Furthermore, from the model obtained, a transition probability matrix is made to determine the transition probability value and calculate the average number of steps needed to get to the death state. From the results of the analysis, the probability of transition to a state of death is 1. This shows that a person will surely die from being healthy or positive for COVID-19 within a certain time. During the Delta variant of the COVID-19 pandemic, the average time that a person reaches a death state from a healthy state is 34.02 years. Meanwhile, the average time taken for someone infected with the Delta variant of COVID-19 to death is 33.79 years. During the Omicron variant of the COVID-19 pandemic, the average time that a person reaches a death state from a healthy state is 37.63 years. Meanwhile, the average time taken for someone infected by the Omicron variant of COVID-19 to death is 37.41. This shows that the average age of a person infected with the Delta variant of COVID-19 has decreased by 2.79 months, while the average age of a person infected with the Omicron variant of COVID-19 has decreased by 2.70 months.